Using Video-Fluoroscopy and Multibody Modelling to Unveil the Influence of a Gradually Reducing Femoral Radius on Ligament Elongation Patterns Following Posterior Cruciate-Retaining Total Knee Arthroplasty - Seyyed Hamed Hosseini Nasab; Philipp Bänteli; Renate List (Applied Sciences)
Stability in total knee arthroplasties (TKAs) is mainly provided by soft tissue structures and the implant geometry. Paradoxical anterior translation could be decreased with a gradually reducing femoral radius compared to a dual-radii design. However, the influence of the sagittal curvature of the femoral condyles on knee ligaments remains unclear. This study quantified the length change patterns of the medial and lateral collateral ligaments (MCL and LCL) and posterior cruciate ligament (PCL) in 15 subjects with a gradually reducing radius and 15 subjects with a dual-radii TKA. Kinematics obtained from video-fluoroscopy were used to drive personalised multibody knee models. The ligament lengths were analysed throughout complete cycles of level gait, stair descent, and sit-to-stand-to-sit activity. Regardless of the implant design, our results indicated flexion-dependent elongation patterns in all ligament bundles. Importantly, however, subjects with the dual-radii implant design exhibited higher ligament strains during the mid-flexion phase compared to those with gradually reducing designs. Our findings, therefore, emphasise the importance of the impact of subtle changes in implant geometry on the loading patterns of the knee soft tissues, which need to be acknowledged by implant manufacturers and orthopaedic surgeons.